Knowledge, attitudes, and experience of dentists living in Saudi Arabia toward child abuse and neglect - R. Al-Dabaan; J.T. Newton; K. Asimakopoulou (Elsevier, 2014)
Aim: To analyze the experience and knowledge of dental practitioners in Saudi Arabia regarding the identification of child abuse and neglect (CAN), to identify barriers that prevent the reporting of suspected cases of child maltreatment by dental practitioners, and to assess the need for training dentists in child protection. Methods: A self-administered, web-based questionnaire was emailed to all of the members of the Saudi Dental Society (n = 7352) in 2012. Results: The respondents (n = 122) demonstrated good knowledge of the forms and indicators of CAN. Moreover, a large proportion (59%) had experienced a case of child abuse or neglect in their practice over the previous five years. However, only about 10% of these respondents made a report. Fear of family reprisal, lack of certainty about the diagnosis of child maltreatment, and uncertainty about case management were critical barriers to the reporting of the suspected child maltreatment. In addition, only 20.9% of the respondents reported having knowledge of a child protection policy in their workplace. Conclusions: Based on the results of this survey, it appears that the level of knowledge among the respondents regarding the forms and indicators of CAN is good. However, a large proportion of respondents did not take action regarding suspected cases of CAN in their practice over the past five years. Therefore, additional resources and training are needed to support the identification and management of cases of child maltreatment by dental practitioners. Keywords: Child abuse, Child neglect, Child protection, Dental team, Saudi Arabia